2006
DOI: 10.1111/j.1744-7348.2006.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of different forms of propagules of Rhizoctonia solani AG2‐1 (ZG5) exposed to the volatiles produced in soil amended with green manures

Abstract: The sensitivity of different forms of propagules of Rhizoctonia solani anastomosis group (AG)2-1/zymogram group (ZG)5 to volatile compounds produced in soil amended with green manure will influence the efficacy of green manures used to manage the disease. In laboratory experiments, we determined the impact of volatiles arising from residues of five species of Brassicaceae, and Avena sativa (oat), a non-Brassicaceae species, and volatiles of pure allyl isothiocyanate (AITC) or 2-phenylethyl isothiocyanate (2-PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Thick-walled oospores or chlamydospores of various oomyces, or sclerotia of Rhizoctonia and Sclerotinia may be less sensitive to ITCs than germinating propagules of Aphanomyces euteiches or Fusarium oxysporum (Smolinska & Horbowicz, 1999). Recent studies also demonstrated that hyphae of Rhizoctonia solani arising from sclerotia were more resistant to ITCs than those arising from agar plugs (Yulianti et al, 2006). Disease control arising from direct ITC-related suppression may be expected to be more effective for obligate parasites such as that reported for the take-all fungus (Gaeumannomyces tritici) and powdery scab in potato (Spongospora subterranea) where inoculum recovery requires a host, and more variable for saprophytes such as Rhizoctonia solani.…”
Section: Ecological Considerations 97mentioning
confidence: 92%
“…Thick-walled oospores or chlamydospores of various oomyces, or sclerotia of Rhizoctonia and Sclerotinia may be less sensitive to ITCs than germinating propagules of Aphanomyces euteiches or Fusarium oxysporum (Smolinska & Horbowicz, 1999). Recent studies also demonstrated that hyphae of Rhizoctonia solani arising from sclerotia were more resistant to ITCs than those arising from agar plugs (Yulianti et al, 2006). Disease control arising from direct ITC-related suppression may be expected to be more effective for obligate parasites such as that reported for the take-all fungus (Gaeumannomyces tritici) and powdery scab in potato (Spongospora subterranea) where inoculum recovery requires a host, and more variable for saprophytes such as Rhizoctonia solani.…”
Section: Ecological Considerations 97mentioning
confidence: 92%
“…Amendment rates employed in this and previous studies (10,11,24,25) are equivalent to the application of seed meal at 8 to 10 t ha -1 . These rates equate to an amount that ranges from <1 to 25% of that recently used in the evaluation of composts in greenhouse, apple orchard, and other field-level production systems (5,33,36,37). Seed meal sourced from the same Brassica sp.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, capacity of each Brassicaceae seed meal examined to suppress root infection by R. solani AG-5 required activity of the native orchard soil biology. This included B. juncea seed meal, which also produces glucosinolate hydrolysis products previously shown to inhibit this fungal pathogen (18,37), and provide control of damping-off incited by R. solani AG-4 (9). In the case of B. juncea PG, the requirement for an active microbial community and the functional mode of action leading to disease control varied in a temporal manner.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Nevertheless, no extensive research has been developed to unravel the chemical nature of the volatile compounds responsible for the beneficial effects of biodisinfestation practices. Yulianti et al, [16] in experiments on the simultaneous use of a polyethylene sheet on soil (solarization or biosolarization) to retain the volatiles, highlighted the importance of sulphur compounds released from decaying Cruciferae and Compositae plants for controlling some soil pathogens. Biosolarization usually leads to a considerable enhancement of the organic matter biocidal effect on the soil pathogens, through increased topsoil temperature and concentration of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%